Yiqi Qingre Gao alleviates renal fibrosis in UUO mice via PI3K/AKT pathway - Jin, Qi; Li, Qian; Yang, Liping; Ma, Fang; Mao, Huimin; Wang, Yuyang; Liu, Tongtong; Peng, Liang; Li, Ping; Zhan, Yongli (Frontiers in Pharmacology, 2025)
Introduction: Renal fibrosis is an endpoint event of various progressive chronic kidney diseases (CKD), but there are no effective antifibrotic treatments. Yiqi Qingre Gao (YQQRG) has shown potential in alleviating CKD, although its exact mechanism of action remains uncertain. This study aims to evaluate the impact of YQQRG on renal fibrosis and to explore the molecular pathways involved.Methods: The study employed a unilateral ureteral obstruction (UUO) mouse model, followed by a 2-week course of YQQRG treatment. Renal function was assessed through measurements of serum creatinine (SCr) and blood urea nitrogen (BUN). Kidneys were collected for histological and molecular biology analysis. To identify the detailed mechanisms, network pharmacology, RNA sequencing (RNA-Seq), transforming growth factor-beta1 (TGF-β1)-stimulated human renal proximal tubular epithelial (HK-2) cells, and molecular docking were used.Results: YQQRG treatment significantly improved renal function, pathological damage, and renal fibrosis in UUO mice. Ten blood-entering components and 403 potential targets of YQQRG were identified by liquid chromatography-mass spectrometry (LC-MS) and network pharmacology. 20,107 targets of renal fibrosis were revealed by RNA-Seq of kidneys from the control and UUO groups. The results of the KEGG pathway enrichment analysis of YQQRG and renal fibrosis were combined, which showed that YQQRG’s renoprotective effects were strongly associated with the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. Experimental validation further confirmed that YQQRG suppressed the PI3K/AKT pathway in the renal tissues of UUO mice; the addition of the PI3K/AKT agonist reversed the antifibrotic effects of YQQRG in TGF-β1-stimulated HK-2 cells. Furthermore, molecular docking indicated that YQQRG’s primary active components exhibited a strong binding affinity to critical targets.Discussion: This study initially demonstrated that YQQRG improved renal function and kidney injury in UUO mice by revealing its antifibrotic mechanism, and it operates through the inhibition of the PI3K/AKT pathway, which highlights YQQRG as a potential therapeutic option for treating CKD.